Safety and efficacy of a feed additive consisting of halofuginone hydrobromide (STENOROL®) for chickens for fattening and turkeys for fattening/reared for breeding (Huvepharma N.V.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a new scientific opinion on the coccidiostat halofuginone hydrobromide (STENOROL®) when used as a feed additive for chickens for fattening and turkeys for fattening/reared for breeding. The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concludes that the safety for turkeys for fattening established in its previous opinion can be extended to turkeys for breeding up to 12 weeks of age. Based on the new data provided on the safety for consumer, environment and efficacy, the Panel updates its previous conclusions as follows: halofuginone hydrobromide is not genotoxic. Applying an uncertainty factor of 100 to the lowest no observed adverse effect level (NOAEL) of 0.03 mg/kg body weight (bw) per day, an acceptable daily intake (ADI) of 0.3 μg halofuginone/kg bw is established. The chronic exposure of consumers to residues of halofuginone would amount to 6–19% of the ADI after 3 days of withdrawal. Therefore, the Panel considers that the additive is safe for the consumer of tissues obtained from chickens for fattening and turkeys for fattening fed the additive at a maximum level of 3 mg/kg complete feed at a 3‐day withdrawal time. For control purposes, the Panel recommends the setting of the following maximum residue limits (MRLs): liver, 50 μg/kg; kidney, 40 μg/kg; muscle, 3 μg/kg; skin/fat, 10 μg/kg wet tissue. Based on an updated environmental risk assessment, no concern for groundwater is expected. Halofuginone is unlikely to bioaccumulate and the risk of secondary poisoning is not likely to occur. No safety concerns are expected for terrestrial and aquatic environments. The additive has the potential to control coccidiosis in chickens for fattening and turkeys for fattening/reared for breeding up to 12 weeks of age at a minimum level of 2 mg/kg complete feed.